2012
DOI: 10.1242/jeb.057380
|View full text |Cite
|
Sign up to set email alerts
|

Precocial hindlimbs and altricial forelimbs: partitioning ontogenetic strategies in Mallard ducks(Anas platyrhynchos)

Abstract: SUMMARYPrecocial development, in which juveniles are relatively mature at hatching or birth, is more common among vertebrates than altricial development, and is likely to be the basal condition. Altricial development characterizes many birds and mammals and is generally viewed as an alternate strategy, promoting fast growth rates, short developmental periods and relatively poor locomotor performance prior to attaining adult size. Many aquatic birds such as Anseriformes (ducks, geese and swans), Charadriformes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(119 citation statements)
references
References 43 publications
4
115
0
Order By: Relevance
“…Mallards reached an average terminal mass of ~1300g (Dial and Carrier, 2012) over a 60d.p.h. ontogenetic period, whereas previous work has shown that fully grown chukar average ~600g and develop for ~100d.p.h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mallards reached an average terminal mass of ~1300g (Dial and Carrier, 2012) over a 60d.p.h. ontogenetic period, whereas previous work has shown that fully grown chukar average ~600g and develop for ~100d.p.h.…”
Section: Resultsmentioning
confidence: 99%
“…For chukar, day 8 corresponds well with the in vivo onset of lift during controlled flapping descent and WAIR (Tobalske and Dial, 2007;Jackson et al, 2009). However, flapping-descent experiments with mallards (Dial and Carrier, 2012) reveal that they do not produce significant lift in vivo until day 45 (supplementary material Fig. S3).…”
Section: Comparative Aerodynamic Performancementioning
confidence: 99%
“…The bones and muscles of the wings of steamer ducks are considered to be stouter and more robust than those of flying birds (Lowe, 1934). Mallard ducklings also exhibit a wing-paddling behavior that is similar to steaming (Aigeldinger and Fish, 1995;Dial and Carrier, 2012). Like steamer ducks and eider ducks, mallard ducklings have high wing loadings, but in their case this is due to slow development of the wings relative to the precocial development of the hindlimbs (Dial and Carrier, 2012).…”
Section: Steaming In Common Eiders and Other Speciesmentioning
confidence: 99%
“…Mallard ducklings also exhibit a wing-paddling behavior that is similar to steaming (Aigeldinger and Fish, 1995;Dial and Carrier, 2012). Like steamer ducks and eider ducks, mallard ducklings have high wing loadings, but in their case this is due to slow development of the wings relative to the precocial development of the hindlimbs (Dial and Carrier, 2012). This wingpaddling behavior is most pronounced between day 30 and day 60 of their development, after which the wings are more fully developed and suited for flight (Dial and Carrier, 2012;.…”
Section: Steaming In Common Eiders and Other Speciesmentioning
confidence: 99%
“…One well-publicized example of ontogenetic change in avian wing function concerns the use by juvenile chukar and other taxa of symmetric flapping to assist in cursorial ascent of high-angle terrain (wing-assisted incline running or WAIR [8][9][10][11][12]). This behaviour, which in juvenile chukar occurs developmentally prior to full weight offset via powered flapping, has been proposed as a pathway for wing evolution in the theropod precursors to birds [8,9].…”
Section: Introductionmentioning
confidence: 99%